The five square (5²) foraging test : an ecologically valid laboratory test for optimal foraging - Seah, Jonathan Qun Li (2015)
Study of animal foraging has a long tradition in ethology and animal behaviour literature. These experiments often require field experiments under inhospitable conditions, wide scale of perimeter and more importantly; lack of good experimental control. On the other hand, laboratory tests pertaining to foraging decisions lack construct validity because they fail to capture characteristic “patchy” foraging landscape. The Five Square (5²) Foraging Test Apparatus (FSTA) was developed as a laboratory based apparatus that incorporates patch foraging concepts to create an ecologically valid laboratory test for optimal foraging. I developed the apparatus and conducted a baseline study which determined that the experimental task could be reliably learned by laboratory rats. I further showed that spatial memory did not play a vital role in this task, thus could not confound foraging endpoints. Animals exhibited significant intra-trial variation showing that this experimental protocol show a baseline that is in middle of pure “skim-the-cream” and “lick-the-bowl” strategies; thus retaining good dynamic range for further experimental manipulations. In conclusion, this task can be used to reliably measure changes in foraging decisions under laboratory settings